Neurodevelopment in normocephalic children exposed to Zika virus in utero with no observable defects at birth: a systematic review with meta-analysis - Marbán-Castro, Elena; Vazquez Guillamet, Laia J.; Pantoja, Percy Efrain; Casellas, Aina; Maxwell, Lauren; Mulkey, Sarah B.; Menéndez, Clara; Bardají, Azucena (International journal of environmental research and public health, 2022)
Zika virus (ZIKV) infection during pregnancy is a cause of pregnancy loss and multiple clinical and neurological anomalies in children. This systematic review aimed to assess the effect of ZIKV exposure in utero on the long-term neurodevelopment of normocephalic children born to women with ZIKV infection in pregnancy. This review was conducted according to the PRISMA guidelines for systematic reviews and meta-analyses. We performed a random effects meta-analysis to estimate the cross-study prevalence of neurodevelopmental delays in children using the Bayley Scales for Infant and Toddler Development (BSID-III). The risk of bias was assessed using Cochrane’s Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Full-text reviews were performed for 566 articles, and data were extracted from 22 articles corresponding to 20 studies. Nine articles including data from 476 children found 6.5% (95% CI: 4.1-9.3) of infants and children to have any type of non-language cognitive delay; 29.7% (95% CI: 21.7-38.2) to have language delay; and 11.5% (95% CI: 4.8-20.1) to have any type of motor delay. The pooled estimates had a high level of heterogeneity; thus, results should be interpreted with caution. Larger prospective studies that include a non-exposed control group are needed to confirm whether ZIKV exposure in utero is associated with adverse child neurodevelopmental outcomes.